The nature of science and technology for pre-service chemistry teacher: A case of techno-chemistry experiment “From Stannum Metalicum to conductive glass” - Mudzakir, A.; Widhiyanti, T.; Hernani; Arifin, M.; Lestari, A. N.; Jauhariansyah, S. (AIP conference proceedings, 2017)
The study was conducted to address the problems related to low Indonesian students’ scientific literacy as revealed in the PISA (Program for International Student Assessment) since 2000-2015. Science teachers (e.g. chemistry teacher) must recognize the nature of science (NOS) to assist their students in preparing an explanation of a phenomenon scientifically correctly. Teachers also need to understand critically about nature of technology (NOT) and it relationship with science as well as society. To integrate those two kinds of knowledge (NOS and NOT), we can conduct a techno-science activity, which integrate the technology to science course in pre-service teacher education program, so that they can improve their knowledge about nature of science and technology (NOST) and pedagogical content knowledge related to NOST. The purpose of this study was to construct an inquiry based laboratory activity worksheet for making conductive glass so that the pre-service teacher could explain how the structure of the semiconductor Fluor doped Tin Oxide (SnO2.F) affect their performance. This study we conducted, described how to design a pre-service chemistry teacher education course that can improve recognizing view of NOST by using a framework called model of educational reconstruction (MER). The scientific activities in the course were guided inquiry based techno-chemistry experiments involving “From Stannum Metallicum to Conductive Glass”. Conductive glasses are interesting subject research for several reason. The application of this technology could be found on solar cell, OLED, and display panel. The doped Tin dioxide has been deposited on glass substrate using the spray pyrolysis technique at 400-550°C substrate temperature, 4-5 times, 20 cm gap between glass and sprayer and 450 angle to form a thin film which will act as electrical contact. The resistivity is about 0.5 - 15Ω. The product resulted on this study was rated by several expert to find if the worksheet could be used on real learning environment.